The kouroi: The History of the Body in Ancient Greek Art - Hussein, Amer (Al-Adab Journal, 2024)
This research: “The Chorus, the History of the Body in Ancient Greek Art,” deals with the subject of anthropomorphic sculpture of the body, which was generally characterized by its depiction naked in statues that pertain to the male element, while avoiding that in female statues, even if examples of them were not devoid of being found. The subject was dealt with after the introduction. According to the headings of four paragraphs, which are in succession: First: The general meaning of the chorus. Second: The chorus, the technique, the material, the artistic style. Third: Why the body. Fourth: The position of the Greek philosophers on the chorus, and then the results. The research reached a number of results, the most important of which is that the koroi is a characteristic of Greek art specifically, and that among its manifestations is racism. It demonstrated the ability of the Greek artist to embody the human body in a statue that confirmed the artist’s knowledge of anatomy, and also revealed the fact of the body’s annihilation after death that led the ancient Greek to He evoked a naked statue whose physical integrity shows strength and spectacle, thus replacing the symbol with which it is symbolized.